METODE SOCRATIC QUESTIONING BERBASIS KAHOOT TERHADAP HASIL BELAJAR EKONOMI DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS - Melinda Devintasari (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2026)
This study aims to analyze the effect of the Socratic Questioning group discussion method based on Kahoot on students’ economics learning outcomes in terms of their level of critical thinking skills. The research was conducted at SMA Negeri 2 Sukoharjo using a quantitative approach with a quasi-experimental design involving two groups: the experimental group (Socratic Questioning based on Kahoot) and the control group (conventional teaching method). Data were collected through a learning outcomes test (20 multiple-choice questions) and a critical thinking skills test (4 essay questions). The instruments were tested for validity and reliability. Data were analyzed using two-way ANOVA with unequal cells at a 5% significance level, followed by the Tukey HSD post-hoc test for mean comparisons. The results show that the Socratic Questioning based on Kahoot method has a significant positive (+) effect on students’ economics learning outcomes, with a significance value of p = 0.000 (< 0.05). Critical thinking skills also have a significant positive (+) effect on learning outcomes (p = 0.001 < 0.05). However, there is no significant (–) interaction between the teaching method and critical thinking skills (p = 0.116 > 0.05), indicating that the method is effective across all levels of critical thinking skills. These findings confirm that a discussion approach supported by interactive technology can improve economics learning outcomes evenly.